An approach to housework and its educational influence in Islam - Dolatkhah, Leila; Heidari, Hassan; Hosseini, Seyyed Hesamodin (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The purpose of the current research was to find an approach to housework and its educational influence in Islam. Method: The research method is descriptive and analytical with the library method. Results: Being a mother is a solemn responsibility because her responsibility is to raise (children) based on goodness and virtue for a healthy and virtuous society that will be the constructive force of the country and the nation. One of the important and fundamental reasons for the formation of the family institution is the survival and continuation of the generation, childbearing and raising children, which conveys the importance of the position of the mother and the housework in the religion of Islam. Islam pays special attention to housework and women. Ultimately, Islam does not consider breastfeeding as a woman’s obligatory duty, but it gives a reward to the woman for breastfeeding the child. A mother fulfills the role of motherhood, the job of housekeeping, and the dimensions of this job in the best possible way when she can fulfill her moral and educational duties towards the family members in the best possible way, because the mothers’ job is prophets’ job that has an educational effect which cannot be ignored. Therefore, housekeeping as a job has a lot of educational influence. Conclusion: The obtained results indicate that housekeeping has greater achievements than a paid job, which is the education of human society whose benefits reach all levels of society and this serious matter reflects the educational position of the family to the society.